Pengembangan Penilaian Hasil Akhir Belajar Siswa SMK Kesehatan Daarul Hidayah Sukoharjo dengan Prototype - Moh. Muhtarom; Agus Suyatno (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2020)
Learning media that have been used in the form of books and learning media using power point still not support student achievement. In this method sometimes the concentration of students is split with other things, consequently the students are less understanding of the subject matter, as well as the subjects of PPKN, not a few students feel bored and saturated to learn it, students just memorize without understanding the basic concept. The main software used is Macromedia Flash 8 as a software to create create an interesting learning media, iinterakktif and educating. This learning media is filled with materials that have been peeled, researched and in accordance with the Education and Culture Materials Anis Baswedan by issuing the regulation of Minister of Education and Culture no 160 of 2014 about the implementation of the curriculum in 2006 and 2013 curriculum. Application of learning media PPKN class II SMK curriculum 2013 facilitate the teachers or teachers to deliver lessons or materials PPKN. And increase interest in learning and ease in teaching and learning process.